PENGARUH KONSENTRASI PEKTIN DALAM SUHU DAN WAKTU PENYIMPANAN BERBEDA TERHADAP KARAKTERISTIK PELEMBAB KULIT - Herlina Eva Fitriani; Supriyono Eko Wardoyo; Amry Syawaalz (Universitas Nusa Bangsa, 2014)
Effect of Concentration of Pectin in Different Temperature and Storage Time on Characteristics of Skin Moisturizing The use of pectin as a substituent a synthetic material in the manufacture of skin moisturizers can support the reuse of natural ingredients for skin care . This study aimed to obtain optimum concentrations in the preparation of skin moisturizers and to see the characteristics of skin moisturizer with the addition of the pectin concentration . The result showed the optimum concentration of pectin in the preparation of moisturizing the skin with a concentration of 0.05 % with a characteristic appearance ( viscosity ) was most preferably , the pH value of 7.08 ; a specific gravity of 0.98 g / ml ; viscosity of 2229 cP , emulsion stability of 100 % , and there was no microbial contamination in accordance with the standard of quality of skin moisturizersKeyword:. Pectin, concentration, characteristics, skin moisturizing ABSTRAK Penggunaan pektin sebagai pensubstitusi bahan sintetik dalam pembuatan pelembab kulit dapat mendukung penggunaan kembali bahan-bahan alami untuk perawatan kulit. Penelitian ini bertujuan untuk mendapatkan konsentrasi optimum dalam sediaan pelembab kulit dan mempelajari karakteristik pelembab kulit dengan penambahan konsentrasi pektin. Hasil penelitian didapatkan konsentrasi optimum pektin dalam sediaan pelembab kulit dengan konsentrasi 0,05 % dengan karakteristik penampakan (kekentalan) yang paling disukai, nilai pH 7,08; bobot jenis 0,98 g/ml; viskositas 2229 cP, stabilitas emulsi 100 %, dan tidak terdapat cemaran mikroba sesuai dengan syarat mutu pelembab kulit..Kata kunci: Pektin, konsentrasi, karakteristik, pelembab kulit